Why is pornography a technology of gender? Analytical-methodological notes for thinking contemporaneity - Yáñez-Urbina, Cristopher (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The study of pornography from feminist epistemologies has been approached by authors such as Paul B. Preciado and Lucía Egaña from the work on technology of gender developed by Teresa de Lauretis. However, these conceptualizations have been ambiguous in the debate on the construction of the object of study and its mechanisms of action. In this regard, this paper develops a series of analytical-methodological guidelines to clarify this dilemma. A reconstruction of the notion of gender technology is addressed, followed by a genealogy of pornography and a deepening of its deployment as a regime of veridiction of the body, gender and sexualities. Finally, a series of challenges for the establishment of a field linked to pornographic studies are concluded.
Keywords: Porn studies; genealogy; technology of gender; pornification